Melek Digital: Kunci Sukses di Era Digital - sahara, sahara; Ilmi, Miftahul; Silalahi, Rudi Yanto Batara (Penerbit Widina, Widina Media Utama, 2024)
The community service activities in the form of a seminar entitled 'Digital Literacy: The Key to Success in the Digital Age', aims to enhance the digital literacy of SMK Permata Harapan students to meet the challenges of an increasingly digitalised world of work. The main objective of this activity is to provide a basic understanding of digital literacy and effective use of technology. This seminar was conducted through interactive material delivery and direct discussion. The results showed an increase of 31.67% in the students' understanding of digital literacy as measured by a pre-test and post-test. In addition, participant feedback showed that 85% of students found the seminar useful in supporting their readiness for the digital age. Despite obstacles such as students' different levels of understanding of technology, this activity was able to have a positive impact in both the short and long term. For the future, it is suggested to develop a more technical follow-up programme to further develop students' digital skills.ABSTRAKKegiatan pengabdian kepada masyarakat berupa seminar bertajuk